2001
DOI: 10.1086/323660
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Human Immunodeficiency Virus Type 1 Viral RNA Levels in the Female Genital Tract: Implications for Applying Measurements to Individual Women

Abstract: The short-term detection and variability of human immunodeficiency virus type 1 (HIV-1) RNA level was assessed in the blood plasma and genital tracts of 55 HIV-1-infected women. Specimens were collected weekly for 8 weeks from the endocervical canal with wicks and cytobrushes and from the ectocervix and vagina with cervicovaginal lavage. In all, 48 women (87.3%) had detectable genital tract HIV-1 RNA at > or =1 collection times. HIV-1 RNA levels varied least in specimens from endocervical canal wick and most i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
38
1
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 14 publications
2
38
1
2
Order By: Relevance
“…Researchers like cvl because it provides plenty of sample for analysis. It has been shown, however, to have greater variation in values than wick collections [50].…”
Section: Measurement Of Sheddingmentioning
confidence: 94%
“…Researchers like cvl because it provides plenty of sample for analysis. It has been shown, however, to have greater variation in values than wick collections [50].…”
Section: Measurement Of Sheddingmentioning
confidence: 94%
“…Cross-sectional studies of women in Mombasa [4] and Bangui [5] have shown positive correlations between the quantities of genital HIV-1 RNA and genital HSV-2 DNA in persons coinfected with these viruses, whereas a Zimbabwean study did not find any association [6]. The high variability of HIV-1 and HSV-2 genital shedding, both within and between individuals, has been widely reported in large studies from the United States that involved daily sampling [7][8][9], highlighting the need for a longitudinal design with multiple measurement points in order to best describe HIV-1 and HSV-2 genital shedding and identify their correlates.…”
mentioning
confidence: 96%
“…Although others have reported on biologic variation of HIV-1 RNA levels in the genital tract at separate sampling times (5,12), no previous studies have reported reproducibility of duplicate samples obtained at the same time.…”
mentioning
confidence: 98%
“…In addition, other authors have reported on differences in HIV-1 RNA and DNA measurements between cervical and vaginal compartments (5,11), and it is possible that this may illustrate an actual biological difference in viral shedding between these two sites. Interestingly, many investigations of genital tract HIV-1 RNA virus have utilized the technique of cervicovaginal lavage, which does not enable discrimination between the two compartments of the genital tract (2,6,7,15).…”
mentioning
confidence: 99%